Skeletal Mineralization Deficits and Impaired Biogenesis and Function of Chondrocyte‐Derived Matrix Vesicles in Phospho1–/– and Phospho1/Pit1 Double‐Knockout Mice. (17th May 2016) - Yadav, Manisha C; Bottini, Massimo; Cory, Esther; Bhattacharya, Kunal; Kuss, Pia; Narisawa, Sonoko; Sah, Robert L; Beck, Laurent; Fadeel, Bengt; Farquharson, Colin; Millán, José Luis
ABSTRACT: We have previously shown that ablation of either the Phospho1 or Alpl gene, encoding PHOSPHO1 and tissue‐nonspecific alkaline phosphatase (TNAP) respectively, lead to hyperosteoidosis, but that their chondrocyte‐derived and osteoblast‐derived matrix vesicles (MVs) are able to initiate mineralization. In contrast, the double ablation of Phospho1 and Alpl completely abolish initiation and progression of skeletal mineralization. We argued that MVs initiate mineralization by a dual mechanism: PHOSPHO1‐mediated intravesicular generation of inorganic phosphate (Pi ) and phosphate transporter‐mediated influx of Pi . To test this hypothesis, we generated mice with col2a1 ‐driven Cre‐mediated ablation of Slc20a1, hereafter referred to as Pi t1, alone or in combination with a Phospho1 gene deletion. Pi t1 col2/col2 mice did not show any major phenotypic abnormalities, whereas severe skeletal deformities were observed in the [ Phospho1 –/– ; Pi t1 col2/col2 ] double knockout mice that were more pronounced than those observed in the Phospho1 –/– mice. Histological analysis of [ Phospho1 –/– ; Pi t1 col2/col2 ] bones showed growth plate abnormalities with a shorter hypertrophic chondrocyte zone and extensive hyperosteoidosis. The [ Phospho1 –/– ; Pi t1 col2/col2 ] skeleton displayed significant decreases in BV/TV%, trabecular number, and bone mineral density, as well as decreased stiffness, decreased strength, and increased postyield deflection compared to Phospho1 –/– mice. Using atomic force microscopy we found that ∼80% of [ Phospho1 –/– ; Pi t1 col2/col2 ] MVs were devoid of mineral in comparison to ∼50% for the Phospho1 –/– MVs and ∼25% for the WT and Pi t1 col2/col2 MVs. We also found a significant decrease in the number of MVs produced by both Phospho1 –/– and [ Phospho1 –/– ; Pi t1 col2/col2 ] chondrocytes. These data support the involvement of phosphate transporter 1, hereafter referred to as Pi T‐1, in the initiation of skeletal mineralization and provide compelling evidence that PHOSPHO1 function is involved in MV biogenesis. © 2016 American Society for Bone and Mineral Research.